Taxonomy of Peruvian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae) - Perkins, Philip D. (Zootaxa, 2020)
The taxonomy of Peruvian water beetles in the genus Hydrochus Leach, 1817 is presented. The known fauna now consists of 22 species, 14 of which are described as new species. The new species are diagnosed, and high-resolution images of the habitus and male genitalia of each species are given. The following new species are described: H. alternatus n. sp., H. astrictus n. sp., H. bisinuatus n. sp., H. bucapitus n. sp., H. cracentis n. sp., H. dualis n. sp., H. lescheni n. sp., H. obliquus n. sp., H. parvicollis n. sp., H. spinosus n. sp., H. subovatus n. sp., H. tambopaticus n. sp., H. tripartitus n. sp., and H. uniformis n. sp. New locality data are provided for H. argutus Knisch 1921, H. bituberculatus Perkins 2019, H. coeneni Makhan 1992, H. leei Perkins 2019, H. lobatus Perkins 2019, H. obscurus Sharp 1882, H. richteri Bruch 1915, and H. sagittarius Perkins 2019. Images of the habitus and male genitalia of H. coeneni Makhan 1992 are also given.